Kennedy: The New Frontier Revisited
IX, 291 p.
Keywords: Leading Kennedy scholars along with a group of younger historians have mined recently declassified documentation in order to re-examine many of the key issues surrounding JFK's time in the White House: Vietnam, Cuban missile crisis, Berlin crisis, space race, and others. Rejecting the idolatry and bitterness evident in so many previous works on JFK, this study adopts an evenhanded, eclectic approach. The result is a less caricatured, more compelling view of the Kennedy presidency.